Pengaruh Media Perendaman Komposit Rami Poliester Terhadap Kekuatan Tarik dan Kekuatan Bending - Fadli, La Ode Muammar; Sudarsono, Sudarsono; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2019)
The purpose of this research is to know the influence of water absorption withfreshwater soaking media, and seawater to tensile strength and bending powerof ramie-polyester composite. The ramie-polyester composite research is madeby the method of hand-lay-up with a fiber-matrix fraction of 30:70 %. The specimen is made according to the ASTM D 638-01 tensile test Standard and ASTM D 9002 standard bending test. The Immersion test with freshwater soaking media, and seawater for 7 days. The tensile test and bending test is done for conditions before immersion and after immersion. The research results showed that the value of absorption specimen freshwater tensile test is 6.2948 %, and seawater is 5.1579 %. While freshwater bending test specimens are 6.2937 % and soaking water is 5.1575 %. The highest tensile strength was on the specimen without immersion 18.266 N/mm2 and the lowest tensile strength is on the freshwater soaking specimen of 11.303 N/mm2. The highest bending strength was on the specimen without immersion 40,120 N/mm2 and the lowest bending strength is on the freshwater soaking specimen of 18,082 N/mm2. Keywords: composite, ramie, polyester, water absorption, tensile strength andbending.